Bolivia : Selected Issues. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper examines economic developments in Bolivia during 1990-97. Macroeconomic developments in 1997 were generally sound. Economic growth for the year remained moderately robust while inflation continued on a downward path. However, the structural reforms adopted since 1995 generated fiscal costs of about 3 percent of GDP in 1997, with the 1996 pension reform accounting for about half of these costs. The paper also reviews Bolivia's growth performance over 1960-97 and assesses the factors behind that performance.